2013
DOI: 10.1177/1354067x13489319
|View full text |Cite
|
Sign up to set email alerts
|

The olive tree effect: Future time perspective when the future is uncertain

Abstract: Different fields of psychology have shown that future time perspective (FTP) has an important role in changing individual attitudes and behaviours. However, recent societal conditions, like the economic crises of the Western world, may have changed the meaning itself of the future, passing from hope to threat. This article discusses possible consequences of this change of sign of the future and the implications of future time perspective as an educational strategy in multicultural context. Synthesizing the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 76 publications
(97 reference statements)
2
36
1
Order By: Relevance
“…Others may view the future as negative, filled with such overwhelming urges to use the substance (Morselli, 2013). It is true that the ZTPI presents a positive bias in the assessment of a, exclusively, positive Future (Papastamatelou et al, 2015).…”
Section: Results Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Others may view the future as negative, filled with such overwhelming urges to use the substance (Morselli, 2013). It is true that the ZTPI presents a positive bias in the assessment of a, exclusively, positive Future (Papastamatelou et al, 2015).…”
Section: Results Interpretationmentioning
confidence: 99%
“…Regarding the opposite inclination, a massive and oppressive urge to drink alcohol (i.e., Obsessed/Compelled dimension) can prevent the patient to look ahead to only consider their immediate needs. Others may view the future as negative, filled with such overwhelming urges to use the substance (Morselli, ). It is true that the ZTPI presents a positive bias in the assessment of a, exclusively, positive Future (Papastamatelou et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this possibility should be considered given the conceptualizations of FTP and autonomy‐ versus dependency‐oriented help. FTP is defined as a consideration of future events while making present behavioural decisions (Morselli, ; Simons, Vansteenkist, et al ., ). Accordingly, FTP, either measured or manipulated, is related to conceiving present behavioural decisions in light of their future consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, we focus on future time perspective (FTP). FTP is conceptualized as consideration of future events while making present behavioural decisions (Morselli, ; Simons, Dewitte, & Lens, ), and associated with psychological variables such as future orientation (Piko, Luszczynska, Gibbons, & Teközel, ); considerations of future consequences (Strathman, Gleicher, Boninger, & Edwards, ); delay of gratification (Cuskelly, Einam, & Jobling, ); and decreased impulsivity (Allen, Moeller, Rhoades, & Cherek, ). On the one hand, it was suggested that compared to individuals with balanced time perspective, people with a dominant future orientation are inclined to delay gratification and as a result may experience lower levels of subjective well‐being (see Boniwell et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The need to study the characteristics of stress-resistance and time perception is conditioned by: 1) scientific reasons for properly understanding the relationship between stress-resistance, time perception and ethno-cultural differences (Morselli, 2013); 2) the need for psychological support for students, taking into account their ethno-cultural characteristics when perceiving time in a stressful period. Thus, the question of how similar or different are stressful experiences in cultures with low and high tolerance to uncertainty remains undeveloped (Hofstede, Hofstede, & Pedersen, 2012).…”
Section: Problem Statementmentioning
confidence: 99%